The Integration of Organizational Structure, Culture, and Strategic Leadership on Organizational Performance: A Literature Review - Saputri, Dea Amanda; Septyani, Rilis; Atika, Atika; Arjani, Putri Azzara; Harahap, Dwi Ananda; Mirnawati, Mirnawati; Kuswanto, Kuswanto; Wahyuni, Sri; Soleh, Ahmad (The Future of Education Journal, 2026)
The increasing dynamics of the business environment driven by globalization, digitalization, and economic uncertainty have intensified the complexity of strategy implementation within organizations. The high rate of implementation failure indicates a significant gap between strategic planning and execution. This study aims to analyze and synthesize the key factors influencing strategy implementation through the integration of organizational structure, strategic leadership, organizational culture, resource allocation, and management control systems. This research employs a Systematic Literature Review (SLR) method using data sourced from Google Scholar, SINTA-indexed journals, and other accredited publications within the 2020–2025 period, with a total of 25 selected articles analyzed using thematic synthesis. The findings reveal that successful strategy implementation is not determined by a single variable but by the synergy among organizational elements, where strategic leadership and organizational culture act as primary drivers, while organizational structure and management control systems function as operational enablers. Furthermore, appropriate resource allocation strengthens the overall effectiveness of strategy implementation. These findings indicate that an integrative and system-based approach is essential for enhancing the success of strategy implementation in modern organizations.